Behavioral responses of Sotalia guianensis (Cetartiodactyla, Delphinidae) to boat approaches in northeast Brazil - Marega-Imamura, Marcela; Carvalho, Gustavo Henrique de [UNESP]; Le Pendu, Yvonnick; Silva, Patricia Sousa da; Schiavetti, Alexandre (Univ Catolica De Valparaiso, 2018)
Boat engines increase the noise levels of the oceans, alter the acoustic environment of cetaceans and diminish their efficiency to echolocate. This study aims to determine if Guiana dolphins (Sotalia guianensis) are influenced by boat approaches. A land-based survey was conducted to record behavioral responses and count surfacing events of Guiana dolphins during 293 observation sessions from February to November 2014 in Pontal Bay, Ilheus, Brazil. Ninety-eight behavioral responses to boat approaches of 93 dolphin groups were classified as negative (interruption or alteration of activity) or neutral (no response). The dolphins presented a neutral response to 90% of boats without engine approaches, 48% negative responses to inboard motorboat approaches, and 76% negative responses to outboard motor boat approach. Resting groups demonstrated 14 negatives and four neutral responses. Groups engaged in forage-feed activity presented ten negative and seven neutral responses while traveling groups exhibited 14 negative and 36 neutral responses. The average rate of surfacing events was significantly superior (P < 0.001) in the absence of boats (1.83 +/- 0.90 surfacing events ind(-1) min(-1)) than in their presence (1.34 +/- 0.92 surfacing events/individual/minute). Guiana dolphins are exposed to an increasing number of anthropic perturbations and the evaluation of its behavioral responses to approaching boats is the first step to comprehend the real impact of boat encounters. Our results may contribute to the development of management strategies in estuarine areas to increase the conservation of the Guiana dolphins.
Keywords: Sotalia guianensis; Guiana dolphin; behavior; surfacing events; dolphin-boat; estuary; Brazil